2022
DOI: 10.3389/fimmu.2022.1007257
|View full text |Cite
|
Sign up to set email alerts
|

The clinical value of indirect immunofluorescence for screening anti-rods and rings antibodies: A retrospective study of two centers in China

Abstract: ObjectiveTo investigate the distribution and clinical significance of the rods and rings (RR) pattern in various diseases.MethodsA total of 169,891 patients in Peking Union Medical College Hospital (PUMCH) and 29,458 patients in Inner Mongolia People’s Hospital (IMPH) from January 2018 to December 2020 were included, and the results of ANA (antinuclear antibodies) and special antibodies were analyzed retrospectively.ResultsThe positive rates of ANA and RR patterns were 34.84%, 0.16% in PUMCH, and 44.73%, 0.23%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 53 publications
0
0
0
Order By: Relevance
“…also reported higher presence of RR in patients with autoimmune diseases and concluded that autoantibodies were much more common in connective tissue diseases than that in other diseases. They interestingly noted the highest prevalence in patients with AIH and primary biliary cholangitis (PBC) ( 15 ). RR structures were also defined by Assandri in 2019 in a case with PBC ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…also reported higher presence of RR in patients with autoimmune diseases and concluded that autoantibodies were much more common in connective tissue diseases than that in other diseases. They interestingly noted the highest prevalence in patients with AIH and primary biliary cholangitis (PBC) ( 15 ). RR structures were also defined by Assandri in 2019 in a case with PBC ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Zhang reported anti-RR prevalence as 0.10% in western China in 2016-2018 period (2). However, Meng et al reported anti-RR frequencies of 0.16% and 0.23% in two different large hospitals in China between 2018 and 2020 (15). Considering these results, there is a wide variety in the prevalence of RR positive patients in different locations.…”
Section: Discussionmentioning
confidence: 99%